Pharmacophore mapping of Angiotensin Converting Enzymes (ACEs): Insight to Binding Site of ACE1 and ACE2 - Ujiantari, Navista Sri Octa; Apsari, Cintya Nurul (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Angiotensin Converting Enzymes (ACEs) are carboxypeptidase enzymes involved in the renin-angiotensin system (RAS), which catalyze angiotensin I by cleavage of the peptide bond. ACE1 has been known as a target for antihypertensive drugs. Another homolog of ACE1, ACE2 has been popular since 2020 because this enzyme is responsible for the SARS-COV2 infection in the human body. Interestingly, it was found that ACE1 inhibitors did not inhibit ACE2. Hence, this study aims to elucidate the pharmacophore of ACE1 and ACE2 in order to understand the mechanism of these different inhibitions. Pharmacophore mapping was carried out using a pharmacophore query editor in the Molecular Operating Environment (MOE). The 3D structures of both enzymes bound to respective inhibitors were prepared and their pharmacophore features were extracted. Besides that, the similarity of both enzymes was analyzed by comparing their amino acid sequences using Align in Uniprot. In addition to pharmacophore mapping, the surfaces of both binding sites were analyzed to obtain a comprehensive evaluation. Results showed that both ACE1 and ACE2 contain nine and eight pharmacophore features, respectively. The amino acid residues of both enzymes were quite similar, especially in the active site. However, both ACE1 and ACE2 inhibitors showed different interactions even though both were well aligned. It was found because the functional groups of both inhibitors were slightly different as well as the active site size of both enzymes. Thus, this might result in different ability of ACE1 inhibitors to occupy the binding site of ACE2. These findings could provide useful information in the design of new selective ACE1 compounds as well as ACE2 compounds.